Respon Tanaman Cabai (Capsicum frutescens L.) Pada Pemberian Pupuk Mono Kalium Phosphate Dan Pupuk Organik Terhadap Pertumbuhan Dan Produksi - Made Naratama Nugraha; Luh Kartini; Anak Agung Ngurah Mayun Wirajaya (GEMA AGRO, 2023)
This study aims to determine the effect of giving MKP fertilizer, rabbit solid organic fertilizer and the interaction of MKP fertilizer with rabbit solid organic fertilizer on the growth and yield of cayenne pepper plants. This research was conducted in Subak Rapuan, Mas Village, Ubud District, Gianyar Regency with an altitude of 400 meters above sea level. The experiment lasted for 4 months, from May to July 2022. This experiment used a Randomized Block Design (RAK) with 2 factors arranged in a factorial manner. The first factor is using MKP fertilizer with 4 levels, namely M0: 0 g l-1 water, M1: 2 g l-1 water, M2: 4 g l-1 water, M3: 6 g l-1 water and the second factor is using solid organic rabbit fertilizer consisting of 3 levels, namely P1: 10 tons ha-1, P2: 20 tons ha-1 and P3: 30 tons ha-1. Observations of plant height, number of leaves, number of flowers, and number of fruit will begin 3 weeks after planting, while the fresh weight and dry weight of fruit and stover will be measured at the end of harvest. The results of statistical analysis showed that the application of MKP fertilizer to cayenne pepper plants had a very significant effect on the variables of maximum leaf number, number, number of flowers, total fruit number and fruit fresh weight and had no significant effect on maximum plant height, fruit oven dry weight, fresh weight of stover and oven dry weight of the stove. The treatment of giving rabbit organic fertilizer showed a significant to very significant effect on all observed variables except for the maximum number of leaves and fruit oven dry weight which showed no significant effect. The interaction between the treatment of the effect of MKP fertilizer with organic rabbit fertilizer had a very significant effect on maximum plant height, significantly affected the maximum number of leaves, number of flowers, total fruit number, fruit fresh weight, fruit oven dry weight and oven dry weight of the stove.